Impact of knowledge type, strategic orientations and organizational learning on new product launch success - Adeel, Muhammad (2021)
This study is aimed at observing the impact of knowledge type, strategic orientation, organizational learning, and knowledge management system on new product launch success by drawing on Resource-based Theory, Knowledge-based View, and Double-loop Learning Theory. The study integrates the two concepts of knowledge type (knowledge complexity and knowledge tacitness) and three strategic orientations (market orientation, product orientation and relationship orientation) in a cohesive framework which defines a realistic view of new product launch success. It provides a road map in pursuing to test both concepts with mediating (organizational learning) and moderating (knowledge management system) factors as they are crucial for new product launch success. Past research has mainly focused on new product development but rarely see it through all the way to actual commercial success in the launch stage of a product. This study focuses on actual commercial success in the NPD process which is impacted by product-centered knowledge and strategic organizational orientation. The study was conducted through positivism philosophy, employed a deductive approach, explanatory research design, and a quantitative methodology. In all, 211 samples were collected from the leather gloves industry in Sialkot, Pakistan. The industry is export oriented and is well known in the global market for its extensive variety and high quality of leather gloves products. Smart-PLS and SPSS were used in analyzing and developing the model of the study. The analysis revealed that knowledge complexity and knowledge tacitness positively relates to new product launch. However, market orientation and product orientation were insignificant to new product launch success. Relationship orientation has a significant positive relationship with new product launch success. Organizational learning is positively linked to new product launch success. Regarding mediation effects, the results show that organizational learning was found to mediate the relationship between knowledge complexity, knowledge tacitness, market orientation, product orientation, and new product launch success. However, there was no mediation effect of organizational learning between relationship orientation and new product launch success. In relation to moderating effects, the results suggest that no moderation effect was found. Based on this, the findings are beneficial for policymakers, the government of Pakistan, firm owners, managers, as well as other stakeholders to formulate succeeding policies and practices. Finally, it is recommended for further research to employ other organizational resource variables which are not included in this study.